CCR9 Expressing T Helper and T Follicular Helper Cells Exhibit Site-Specific Identities During Inflammatory Disease - Cosorich, Ilaria; McGuire, Helen M.; Warren, Joanna; Danta, Mark; King, Cecile (Frontiers in Immunology, 2019)
Abstract CD4+ T helper (Th) cells that express the gut homing chemokine receptor CCR9 are increased in the peripheral blood of patients with inflammatory bowel disease and Sjögren’s syndrome and in the inflamed lesions of autoimmune diseases that affect the accessory organs of the digestive system. However, despite the important role of the GIT in both immunity and autoimmunity, the nature of CCR9-expressing cells in GIT lymphoid organs and their role in chronic inflammatory diseases remains unknown. In this study, we analysed the characteristics of CCR9+ Th and T follicular helper (Tfh) cells in GIT associated lymphoid tissues in health, chronic inflammation and autoimmunity. Our findings reveal an association between the transcriptome and phenotype of CCR9+ Th in the pancreas and CCR9+ Tfh cells from GIT-associated lymphoid tissues. GIT CCR9+ Tfh cells exhibited characteristics, including a Th17-like transcriptome and production of effector cytokines, which indicated a microenvironment-specific signature. Both CCR9+ Tfh cells and CCR9+ Th cells from GIT-associated lymphoid tissues migrated to the pancreas. The expression of CCR9 was important for migration of both subsets to the pancreas, but Tfh cells that accumulated in the pancreas had downmodulated expression of CXCR5. Taken together, the findings provide evidence that CCR9+ Tfh cells and Th cells from the GIT exhibit plasticity and can accumulate in distal accessory organs of the digestive system where they may participate in autoimmunity.